Cash flow management and prediction of financially distressed South African listed firms - Sibiya, Vusumuzi Innocent Sibiya (My University, 2020)
This study focused on Cash flow Management and predictions of financial distress and bankruptcy of South African firms listed on the JSE. The primary objective was to determine whether adjusted cash flow or unadjusted cash flow is a more effective predictor of financial distress. Fifty-four JSE listed firms were examined, using the Ohlson Model and the Altman Z-score model for ascertaining financial distress. The findings of the study are that using adjusted cashflows is more accurate in predicting bankruptcy than unadjusted cashflows. From the findings the study concludes that a true measure of performance which produced favourable results was based on adjusted cash flows. Unadjusted cashflows produced relatively lower accuracy; therefore, depending on them would be unwise. The recommendation from this finding is to use adjusted cashflows as a predictor of bankruptcy or failure, and thus have them serve as a basis for decision making. Furthermore, in predicting the future of a firm, cash flow ratios must be complemented by balance sheet ratios to produce a more robust prediction. The study concluded by making suggestions for future research.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, School of Business Administration, University of the Witwatersrand, Johannesburg, 2020
Keywords: Cash flow Management; Fifty-four JSE; SDG-8: Decent work and economic growth